IMPLEMENTATION OF DEMPSTER SHAFER IN EXPERT SYSTEM IN EARLY DIAGNOSIS OF DENTAL AND MOUTH DISEASES IN CHILDREN - Atalya Kurnia Sari; Iskandar Fitri; Denny Hidayatullah (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Diseases of the teeth and oral cavity are one of the health problems that many people experience. This is very inversely proportional to the needs of everyone who wants to have a healthy mouth and teeth. Lack of awareness to maintain oral and dental health is still low. Many people think that brushing your teeth is enough, even though this activity is not enough to maintain healthy teeth and oral cavity. When diagnosing doctors often do X-rays. Therefore, doctors need a system to diagnose diseases of the teeth and oral cavity, where the system used uses a Dempster Shafer method where the accuracy of this method has been proven to be 93%.